Studer, Helen (audio interview #1 of 4) - Studer, Helen (b. 5/27/1898 - d. 8/00/1981 ); Cleary, Cindy, interviewer
INTERVIEW DESCRIPTION - Studer was rather nervous in this first interview, conducted at the kitchen table in her small, cozy home. This first interview was particularly difficult for her because it dredged up memories of a very painful early life, and she often confused the sequence of events. She leafed through photographs during the interview and asked repeatedly that the recorder be turned off. 5/28/1980